Sosialisasi Penguatan Etika Komunikasi Di Era Digital : Dampak Kemajuan Teknologi Terhadap Interaksi Sosial, Kultural Dan Keagamaan - Wibowo, Imanuel Septian Arie; Utari, Boni Retno; Handriyani, Vinda; Pratomo, Satriyo; Chumaeson, Wahyuning (Universitas Pahlawan Tuanku Tambusai, 2025)
The increased use of social media and advances in information technology have changed the way we interact, but have also created various challenges, including the spread of hoaxes, cyberbullying, and radicalization. This workshop aims to strengthen communication ethics in the digital age, focusing on the impact of technology on social, cultural and religious interactions. This activity provides an understanding of the importance of information verification, critical thinking, and responsibility when communicating in cyberspace. Through interactive methods, participants are engaged in discussions, role-playing simulations, and socialization using digital media to deepen their understanding of good communication ethics. The results of this workshop show an increase in participants' awareness of the impact of negative behavior in cyberspace, as well as the importance of mutual respect in communication across cultures and religions. Overall, this workshop contributes to the creation of a healthier, more inclusive and responsible digital environment by improving the quality of social interactions in the digital age.